Proof [videorecording (DVD)] - Madden, John, 1949-; Paltrow, Gwyneth, 1972-; Hopkins, Anthony, 1937-; Gyllenhaal, Jake, 1980-; Auburn, David, 1969- (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2006)
A devoted daughter who comes to terms with the death of her father, a brilliant mathematician whose genius was crippled by mental insanity, with the help of one of her father's former students.